ESG Controversies in ASEAN-5: The Role of Board Structure and Governance Characteristics - Nisak, Choirun; Solikhah, Badingatus (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2026)
This study analyzes the effects of corporate governance mechanisms on ESG controversies among non-financial ASEAN-5 firms from 2021–2024, with firm size as a moderator. Using a Fixed Effects Model with PCSE, the findings show that audit committee independence and board gender diversity significantly reduce ESG controversies, whereas board independence increases controversy exposure due to greater transparency. CEO duality exhibits a marginally positive effect. Firm size weakens the positive effects of CEO duality, audit committee independence, and gender diversity, while reducing the adverse effect of board independence. Robustness tests confirm the consistency of results. Overall, the study emphasizes that the role of governance in mitigating ESG controversies depends on organizational scale and institutional context.